Pendampingan Revitalisasi Alun-Alun Sentana Desa Katelan Kecamatan Tangen Kabupaten Sragen - Widiastuti, Ratih (Sekolah Vokasi Universitas Diponegoro, 2024)
A square or city square functions as a significant urban catalyst, influencing the urban landscape as it acts as a hub for various social, economic, and cultural activities within a city. Its presence impacts the activities in the surrounding areas, fostering local business growth and providing a space for social interaction that enriches the city's life. However, the existing Sentana square design in Tangen District in Sragen, situated in Katelan Village, requires revitalization to meet the demand for activities and to facilitate communal engagement. A design recommendation has been proposed by the study program of Civil Infrastructure Engineering and Architectural Design, part of the Department of Civil and Planning at the Vocational School of Diponegoro University, through a community service program. Quality Function Deployment (QFD) serves as the primary design approach for the newly designed square, focusing on facilitating markets, supporting small businesses, and promoting local products, which, in turn, supports the Village-Owned Enterprises (BUMDes).